FEATURES OF USING TOURISTIC RESOURCES OF JIZZAKH REGION (Proceedings of International Educators Conference, 2024)
This article talks about the tourist potential of Jizzakh region, tourist resources and their location. Also, tourism plays an important role in the socio-economic development of many geographical regions. From big cities to remote villages, tourism stimulates economic growth, helps create new places, develops infrastructure and stimulates cultural exchange. In this article, we will analyze the available opportunities in this field using the example of the Jizzakh region of the Republic of Uzbekistan.